2014
DOI: 10.1088/0004-637x/782/2/90
|View full text |Cite
|
Sign up to set email alerts
|

GALAXY AND MASS ASSEMBLY (GAMA): MID-INFRARED PROPERTIES AND EMPIRICAL RELATIONS FROMWISE

Abstract: The Galaxy And Mass Assembly (GAMA) survey furnishes a deep redshift catalog that, when combined with the Wide-field Infrared Explorer (WISE), allows us to explore for the first time the mid-infrared properties of > 110, 000 galaxies over 120 deg 2 to z ≃ 0.5. In this paper we detail the procedure for producing the matched GAMA-WISE catalog for the G12 and G15 fields, in particular characterising and measuring resolved sources; the complete catalogs for all three GAMA equatorial fields will be made available t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
307
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 225 publications
(333 citation statements)
references
References 62 publications
24
307
2
Order By: Relevance
“…We confirm this from our analysis of BPT classes where there is a lower fraction of star-forming galaxies among close pairs compared to galaxies in the same volume. Bergvall et al (2003) found only a modest degree of enhancement of star formation for interacting pairs, contributing little to the luminosity; Lin et al (2007) also find only a modest enhancement of star formation in galaxy pairs in a wide range of merger stages; Li et al (2008) instead find that the enhancement in star formation, in a sample of star-forming galaxies, increases with decreasing separation but does not depend on the luminosity ratio, although it is stronger for lower-mass galaxies; for massive galaxies, Robaina et al (2009) find that only 10% of star formation is due to major interactions (albeit at higher redshifts than studied here); Patton et al (2011) also detect an excess of red galaxies in pairs and attribute this to denser environments and hence more significant spheroids (because of the morphology-density relation); Chou et al (2012) confirm that most close pairs are red and not blue; Deng & Zhang (2013) also finds evidence that interactions are not generally responsible for star formation bursts in two volume-limited samples drawn from the SDSS; Cluver et al (2014) study star formation for galaxies in groups and claim that galaxies with a close neighbour have lower star formation rates. Similarly, we find that, by comparing the distributions of Sérsic indices for galaxies in pairs and their parent samples, there is a relative lack of 'disks' and excess of 'spheroids' among paired galaxies as in Patton et al (2011).…”
Section: Discussionmentioning
confidence: 54%
“…We confirm this from our analysis of BPT classes where there is a lower fraction of star-forming galaxies among close pairs compared to galaxies in the same volume. Bergvall et al (2003) found only a modest degree of enhancement of star formation for interacting pairs, contributing little to the luminosity; Lin et al (2007) also find only a modest enhancement of star formation in galaxy pairs in a wide range of merger stages; Li et al (2008) instead find that the enhancement in star formation, in a sample of star-forming galaxies, increases with decreasing separation but does not depend on the luminosity ratio, although it is stronger for lower-mass galaxies; for massive galaxies, Robaina et al (2009) find that only 10% of star formation is due to major interactions (albeit at higher redshifts than studied here); Patton et al (2011) also detect an excess of red galaxies in pairs and attribute this to denser environments and hence more significant spheroids (because of the morphology-density relation); Chou et al (2012) confirm that most close pairs are red and not blue; Deng & Zhang (2013) also finds evidence that interactions are not generally responsible for star formation bursts in two volume-limited samples drawn from the SDSS; Cluver et al (2014) study star formation for galaxies in groups and claim that galaxies with a close neighbour have lower star formation rates. Similarly, we find that, by comparing the distributions of Sérsic indices for galaxies in pairs and their parent samples, there is a relative lack of 'disks' and excess of 'spheroids' among paired galaxies as in Patton et al (2011).…”
Section: Discussionmentioning
confidence: 54%
“…We note that the correlations derived in Cluver et al 2014 compare WISE fluxes with Hα-derived SFRs, and as such may be biased towards emission line-derived SFRs. However, we rescale all SFRs derived in the paper to have the same slope and normalization as the SFR FIR in order to compare each measure directly (see below).…”
Section: Long-duration Mir/fir Continuum Sfrsmentioning
confidence: 94%
“…(2) Secondly, we derive MIR SFRs using the Wide-field Infrared Explorer (WISE) data from the matched GAMA-WISE catalogue outlined in Cluver et al 2014. We use WISE 22 µm (W4) band fluxes, which are not strongly affected by polycyclic aromatic hydrocarbon emission, and the best-fitting SFR correlation obtained in Cluver et al 2014: log 10 SFR MIR (M yr −1 ) = 0.84 log 10 νL 22 µm (L ) − 7.3.…”
Section: Long-duration Mir/fir Continuum Sfrsmentioning
confidence: 99%
“…We select only sources with signal to noise (S/N) ≥ 5, except for W4, where we consider a S/N ≥ 3. We calculate the galaxy stellar mass (M * ) using the WISE W1 filter (3.4 µm) and the W1-W2 (4.6 µm) color following the Cluver et al (2014) calibration. The stellar mass ranges between 10 9 and 10 11 M ⊙ for our sample.…”
Section: Flux Densities and Derived Stellar Massmentioning
confidence: 99%